2021
DOI: 10.1136/bmjopen-2020-046633
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology and severity of childhood pneumonia in primary care in Malawi: a cohort study

Abstract: ObjectiveTo determine the aetiology of community acquired pneumonia in children presenting to primary care in Northern Malawi, and to ascertain predictors for identification of children requiring hospitalisation.DesignThe BIOmarkers TO diagnose PnEumonia study was a prospective cohort study conducted from March to June 2016.SettingPrimary care in Northern Malawi.Patients494 children aged 2 –59 months with WHO defined pneumonia.Main outcome(s) and measure(s)Number of children with bacterial infection identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…However, even with this, there will also be a need to identify those at risk of severe disease so that they can be appropriately referred to hospital. The BIOTOPE study showed that WHO severity criteria were present in a minority (30.4%) of children hospitalised with pneumonia, consistent with recent work in the Lancet Global Health, showing that 39% of fatal cases of pneumonia were defined as having non-severe pneumonia, requiring only home treatment by the 2013 revision [11,17]. The fact that the WHO criteria would have discharged these children with oral antibiotics accentuates the need for new markers of severity, the STARWAVe rule may serve as a useful tool in this regard [13].…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…However, even with this, there will also be a need to identify those at risk of severe disease so that they can be appropriately referred to hospital. The BIOTOPE study showed that WHO severity criteria were present in a minority (30.4%) of children hospitalised with pneumonia, consistent with recent work in the Lancet Global Health, showing that 39% of fatal cases of pneumonia were defined as having non-severe pneumonia, requiring only home treatment by the 2013 revision [11,17]. The fact that the WHO criteria would have discharged these children with oral antibiotics accentuates the need for new markers of severity, the STARWAVe rule may serve as a useful tool in this regard [13].…”
Section: Discussionsupporting
confidence: 77%
“…Validation of the STARWAVe rule was undertaken in the BIOTOPE cohort as described previously [11] . In brief, the BIOTOPE cohort consisted of 494 children with WHO clinically defined pneumonia presenting to primary care in Malawi.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 The BIOTOPE cohort (BIOmarkers TO diagnose PnEumonia) recruited children aged 2-59 months with WHO defined pneumonia from two primary care facilities in Mzuzu, Malawi. 7 Validation of STARWAVe in BIOTOPE employed derivation and internal validation using bootstrapping.…”
mentioning
confidence: 99%